2021
DOI: 10.1007/s00068-020-01578-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between mortality and frailty in emergency general surgery: a systematic review and meta-analysis

Abstract: Purpose The purpose of this review was to determine the association between frailty and mortality among adults ≥ 65 years old undergoing emergency general surgery (EGS). Methods This systematic review followed the PRISMA guidelines (CRD42020172482 on PROSPERO). A search in MEDLINE, PubMed, EMBASE, Scopus, Web of Science, and the Cochrane Database of Systematic Reviews was conducted from inception to March 5, 2020. Studies with patients ≥ 65 years undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Two previous meta-analyses published in the past 5 years investigated frailty in emergency surgical patient group ( 38 , 39 ). Although our results are in line with their conclusion, there are some significant differences in the methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous meta-analyses published in the past 5 years investigated frailty in emergency surgical patient group ( 38 , 39 ). Although our results are in line with their conclusion, there are some significant differences in the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely heterogeneity might not be important in the CFS subgroup ( I 2 =8.7%; p = 0.363). Fehlmann et al reported a significant association between frailty and length of hospital stay (adjusted ORs were 1.21, 1.26, 1.48, 1.44, and 1.62 for CFS 2, 3, 4, 5, and 6–7, respectively) ( 39 ). When we analyzed all the available data, we also found significant relationship between frailty and length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of frailty in elderly patients undergoing emergency surgery is also responsible for postoperative mortality, complications, prolonged length of hospital stay, and the loss of independence after surgery [ 29 ]. Kennedy et al suggested that frailty scoring should be incorporated into preoperative acute surgical assessment to help in decision-making and for developing novel postoperative strategies [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…In 2003, the American Geriatrics Society proposed future studies to develop appropriate screening tools for recognizing high‐risk older patients 7 . Subsequent efforts aimed at identifying reliable frailty screening tools suitable for the ED context; currently, several such tools are available and their effectiveness is evaluated based on the rates of ED revisit, hospitalization, and mortality 8,9 . In addition, previous studies have compared diagnostic accuracy and ease of use of different frailty screening tools 10,11 .…”
Section: Introductionmentioning
confidence: 99%